Examining the Relationship Between Alexithymia, Loneliness, and Differentiation with Suicidal Thoughts in High School Students - Jalili Shishvan, Ali; Heyran Sangestani, Zahra; Gholizadeh, Somayeh; Sadeghmarand, Leila (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to examine the relationship between alexithymia, loneliness, and differentiation with suicidal thoughts in high school students.Materials and Methods: This research is a descriptive correlational study. The statistical population included all female high school students in District 4 of Tabriz during the 2023-2024 academic year (N=4000). Using Krejcie and Morgan's table and multistage cluster random sampling, 351 students were selected as the sample. The data collection tools included the Jackson Differentiation of Self Inventory (2003), the Toronto Alexithymia Scale (1994), the Beck Scale for Suicidal Ideation (1991), and the UCLA Loneliness Scale (1980). Data were analyzed using Pearson correlation coefficient and multiple linear regression analysis with SPSS version 20.Findings: The results indicated a significant positive correlation between alexithymia and loneliness with suicidal thoughts in high school students. Additionally, a significant inverse relationship was found between differentiation and suicidal thoughts in high school students. The multiple regression results also showed that differentiation (beta = -0.38), alexithymia (beta = 0.35), and loneliness (beta = 0.23) could significantly predict changes in suicidal thoughts among high school students, accounting for 52% of the variance in suicidal thoughts.Conclusion: The findings of this study underscore the importance of planning and providing appropriate educational and therapeutic programs aimed at enhancing self-differentiation to reduce suicidal thoughts among students, while also addressing loneliness and alexithymia. The study's results should be communicated to education officials for implementation.